2010
DOI: 10.1007/s12275-009-9261-3
|View full text |Cite
|
Sign up to set email alerts
|

Cotesia plutellae bracovirus suppresses expression of an antimicrobial peptide, cecropin, in the diamondback Moth, Plutella xylostella, challenged by bacteria

Abstract: An endoparasitoid wasp, Cotesia plutellae, induces significant immunosuppression of host insect, Plutella xylostella. This study was focused on suppression in humoral immune response of P. xylostella parasitized by C. plutellae. An EST database of P. xylostella provided a putative cecropin gene (PxCec) which is 627 bp long and encodes 66 amino acids. A signal peptide (22 amino acids) is predicted and two putative O-glycosylation sites in threonine are located at positions 58 and 64. Without bacterial infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…Similarly, cecropin and gloverin in the Manduca sexta egg were down-regulated following parasitization by Trichogramma evanescens [28]. Barandoc et al found that parasitization by Cotesia plutellae suppressed the expression of cecropin in P. xylostella larvae [29]. In contrast, some studies demonstrated that parasitoid challenge induces AMP transcript levels in the host.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, cecropin and gloverin in the Manduca sexta egg were down-regulated following parasitization by Trichogramma evanescens [28]. Barandoc et al found that parasitization by Cotesia plutellae suppressed the expression of cecropin in P. xylostella larvae [29]. In contrast, some studies demonstrated that parasitoid challenge induces AMP transcript levels in the host.…”
Section: Resultsmentioning
confidence: 99%
“…Since insects have no adaptive immunity, their innate immune system must build both cellular and humoral responses against various pathogens; inducible AMPs play an important role in this humoral response (Barandoc et al 2010). Upon injury or infection, most AMPs are co-expressed as groups that act together (Lai and Gallo 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The post-translation process in the native host includes the cleavage of signal peptide by signal peptidase, then deletion of the following two residues, Ala-Pro, by dipeptidyl peptidase (Fig. 2) (Lidholm et al 1987;Barandoc et al 2010). According to the secondary structure by PredictProtein and Antimicrobial Peptide Predictor, the mature peptide can be classified as an all-alpha helix structure with amphipathic properties and a total net charge of +8.…”
Section: Sequence Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…PDVs are the most highly characterized of the known mutualistic viruses [10], replicating only within the calyx cells of the reproductive tract of female wasps [11]. No virus replication occurs in parasitized larvae; however expression of encapsidated PDV genes induces different physiological modifications such as interruption of the larval endocrine system and suppression of the host immune system [12-15]. …”
Section: Introductionmentioning
confidence: 99%